Compensation for cures: Why we should pay a premium for participation in 'challenge studies'. (28th May 2019) - Anomaly, Jonathan; Savulescu, Julian
Abstract: Antibiotic resistance is one of the most pressing public health problems humanity faces. Research into new classes of antibiotics and new kinds of treatments – including risky experimental treatments such as phage therapy and vaccines – is an important part of improving our ability to treat infectious diseases. In order to aid this research, we will argue that we should permit researchers to pay people any amount of money to compensate for the risks of participating in clinical trials, including 'challenge studies' that involve deliberately infecting patients. We think that standard worries about paying for participation in risky research are reducible to concerns that can be addressed with the right screening mechanisms.